Copper-based etalon filter using antioxidant graphene layer. (11th August 2020) - Nam, Kiin; Lee, Youjin; Kim, SeongYeon; Kim, Sunghwan; Hong, Sung Ju; Choi, Wonjong; Lee, Jinhee; Kim, Hyelin; Kim, Dai-Sik; Kim, JunHo; Choi, Soobong; Bahk, Young-Mi
Abstract: Copper is a low-cost material compared to silver and gold, having high reflectivity in the near infrared spectral range as well as good electrical and thermal conductivity. Its properties make it a good candidate for metal-based low-cost multilayer thin-film devices and optical components. However, its high reflectance in the devices is reduced because copper is easily oxidized. Here, we suggest a copper-based Fabry–Perot optical filter consisting of a thin dielectric layer stacked between two copper films, which can realize low-cost production compared to a conventional silver-based etalon filter. The reduced performance due to the inherent oxidation of the copper surface can be overcome by passivating the copper films with monolayer graphene. The anti-oxidation of copper film is investigated by optical microscopy, x-ray photoelectron spectroscopy, and transmission measurement in UV–vi spectral ranges. Our results show that the graphene coating can be expanded for various metal-based optical devices in terms of anti-corrosion.